Do BCS National Championships Lead to Recruiting Violations? A Trend Analysis of NCAA Division I (FBS) Infractions - Robert S. Clark; Paul J. Batista (Journal of Applied Sports Management, 2009)
With the NCAA suggesting increased severity of sanctions for NCAA rules violators (Wieberg, 2008), an area of great concern to athletic directors is the institution’s violation of Article 13 of NCAA Division I legislation while recruiting prospective student-athletes. While researchers state that NCAA violations are on the rise (Mahony,1999; Jordan, Greenwell, Geist, Pastore, & Mahony, 2004), very little research has been conducted to ascertain the number of NCAA recruiting violations committed, and by whom. The purpose of this study was to describe the nature of recruiting violations, including major and secondary violations, conference affiliation of institutions committing major violations, then to analyze major recruiting violations of Division I Football Bowl Subdivision (FBS) institutions. A trend analysis was conducted by examining the frequency and distribution of NCAA major infractions from 1970 to 2007, with a specific focus major recruiting infractions from 1987 through the current construct of the Division I-A (Football Bowl Subdivision) conference structure of 2007. The results of this analysis provide athletic administrators with regional and sport-specific findings regarding major recruiting infractions. It also informs athletic compliance directors of focal points and monitoring strategies based upon sport, region, and conference in am effort to curtail future NCAA recruiting violations.
Keywords: NCAA; BCS; Bowl Championship Series; Recruiting; Violations; Infractions; Athletic compliance